1988
DOI: 10.3164/jcbn.5.201
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Selenium Level in Chronic Pancreatitis

Abstract: SummaryBlood selenium concentrations were found to be significantly

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1997
1997
2001
2001

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…We found a positive and significant correlation of plasma Se and plasma GSH-Px as well as between whole blood Se concentration and red cell GSH-Px activity. Similar correlations have been reported previously for healthy subjects [54,60], pregnant women [71], and in different kinds of cancer patients [1,18,41,57,65]. In some other studies a weak, nonsignificant correlation between these parameters has been shown [32,55,58,61].…”
Section: Blood Gsh-px Activitiessupporting
confidence: 71%
See 1 more Smart Citation
“…We found a positive and significant correlation of plasma Se and plasma GSH-Px as well as between whole blood Se concentration and red cell GSH-Px activity. Similar correlations have been reported previously for healthy subjects [54,60], pregnant women [71], and in different kinds of cancer patients [1,18,41,57,65]. In some other studies a weak, nonsignificant correlation between these parameters has been shown [32,55,58,61].…”
Section: Blood Gsh-px Activitiessupporting
confidence: 71%
“…Several studies [41,57], but not all [1], presented significantly lower GSH-Px activities in red cells and/or plasma of cancer patients. Some other groups have shown significantly [7] or nonsignificantly higher red cell [18,19] and plasma [1,65] GSH-Px activities in cancer patients.…”
Section: Blood Gsh-px Activitiesmentioning
confidence: 99%